IMPLEMENTASI P5 TEMA “HIJAUNYA SEKOLAH” PADA SDN MARGOREJO 1/403 SURABAYA - Siti Nur Halimah; Susilawati; Vina Siti Alifah; Siti Haifa; Mar’atul Khasanah; Muhammad Nurfaisal Sidik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Implementation of the Pancasila Student Profile Strengthening Project (P5) is a program that aims to shape the character of students in accordance with Pancasila values. One of the implementations of P5 at SDN Margorejo 1 Surabaya City is through the theme